(untitled) - Harris, Nick; Nick Harris (Hoboken, 2014)
iOS 7 changed everything--get up to speed! iOS 7 is a major shift in the look and feel of apps--the first major sea change since the iPhone was first introduced. For apps to blend in with the new UI, each needs a complete redesign. Beginning iOS Programming: Building and Deploying iOS Applications starts at the beginning--including an introduction to Objective C--and gives you the skills you need to get your apps up and running. Author Nick Harris has extensive experience developing for iOS and provides a solid background for teaching the building blocks of app development. Learn Objective-C and how it differs from other programming languages Turn your app idea into an actionable plan Build each feature with the help of standalone chapters Assemble your project into a real-world iOS app Throughout the book, you'll be able to experiment with dozens of recipes from real-life scenarios, creating an app as you learn
Keywords: iPhone; Application software; Wrox beginning guides